2005
DOI: 10.1111/j.1600-0404.2005.00432.x
|View full text |Cite
|
Sign up to set email alerts
|

Function of sigma1 receptors in Parkinson's disease

Abstract: Release of dopamine is reduced asymmetrically in the putamen of early PD. [11C]SA4503 PET is an indicator of presynaptic dopaminergic damage in PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
114
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(119 citation statements)
references
References 27 publications
1
114
2
Order By: Relevance
“…In a small group of patients with early Parkinson's disease (n = 6), the BP of 11 C-SA4503 was found to be significantly lower on the more affected than the less affected side of the anterior putamen, although there was no significant difference in BP between patients and controls [108]. These data suggest that Parkinson's disease may be associated with a loss of sigma-1 receptors from the putamen, although the decrease is less striking than that observed in the cerebral cortex in AD.…”
Section: Changes Of Sigma Receptor Density In Aging and Neurodegeneramentioning
confidence: 99%
“…In a small group of patients with early Parkinson's disease (n = 6), the BP of 11 C-SA4503 was found to be significantly lower on the more affected than the less affected side of the anterior putamen, although there was no significant difference in BP between patients and controls [108]. These data suggest that Parkinson's disease may be associated with a loss of sigma-1 receptors from the putamen, although the decrease is less striking than that observed in the cerebral cortex in AD.…”
Section: Changes Of Sigma Receptor Density In Aging and Neurodegeneramentioning
confidence: 99%
“…Those results support the notion that Sig-1Rs, by interacting with endogenous myristic acid, play a pivotal role in the p35 myristoylation and degradation. Discussion Sig-1Rs have been reported to play a role in the pathogenesis of neurodegenerative disorders including AD (30,45,46), Parkinson's disease (47,48), and motor neuron disorders (49)(50)(51). The underlying molecular mechanisms of Sig-1R action remain to be totally clarified.…”
Section: Sig-1r Controls P35 Degradation Mainly Through the Proteasomalmentioning
confidence: 99%
“…Several brain-related pathologies are characterized by a decrease in the density of s 1 Rs. A reduction of 26% in postmortem 3 H-1, 3 di-o-tolylguanidine (DTG) binding studies was detected in the hippocampus of Alzheimer's patients (3), and in vivo 11 C-SA4503 imaging studies demonstrated a reduction of at least 25% in the regions of interest in both Parkinson's and Alzheimer's patients (4,5). Also, s 1 Rs might be implicated in the mechanisms of action of selective serotonin reuptake inhibitors.…”
mentioning
confidence: 96%